Cyclic Cushing's Disease in the Prepubertal Period—A Case Report and Review of Literature - Wȩdrychowicz, Anna; Hull, Barbara; Kalicka-Kasperczyk, Anna; Zieliński, Grzegorz; Starzyk, Jerzy B. (Frontiers in Endocrinology, 2019)
Background: Cyclic Cushing’s disease (CD) has been described in about 15% of adult patients with CD. In the pediatric population, diagnosis of CD is rare and cyclic presentations of the disease are not adequately understood or described. Moreover, prepubertal patients usually do not present with the typical signs and symptoms of CD, which can obscure or delay diagnosis. In this paper, we report a case of cyclic CD in a prepubertal age girl whose etiology was a pituitary corticotropinoma. Case presentation: A Caucasian 7.8-yr-old girl was admitted to pediatric endocrinology for evaluation of short stature and prior obesity. The patient remained overweight despite significant lifestyle modifications, resulting in 6 kg weight loss during the 6 months prior. Physical exam was notable for precocious adrenarche and thelarche, but difficult to differentiate from steatomastia. Hypothalamo-pituitary-adrenal axis diagnostics, including single diurnal excretion of urinary cortisol, morning ACTH, and serum cortisol levels were all within normal limits, and MRI of the pituitary gland showed no deviations at this time. Because of the clinical suspicion of cyclic hypercortisolemia, she was referred to our outpatient clinic for follow-up. After 6 months, the patient returned with rapid weight gain, accompanied by nocturnal anxiety, exacerbation of depressive behavior, insomnia and excessive sweating, and was readmitted to the ward for testing. Standard diagnostics confirmed CD and repeat MRI at 8.6 years old showed a microadenoma of 3 mm x 4 mm in the right side of the anterior pituitary gland. Histopathologic examination described an atypical, densely-granulated pituitary corticotroph adenoma with Ki-67 expression above 3%. Conclusion: Cyclic presentations of CD in the prepubescent age group could cause difficulties in diagnosis because of atypical signs and symptoms, which can be absent in the remission phase. Decreases in height percentiles and velocities obtained from the growth chart, as well as fluctuations in weight, and signs of androgenisation can allow the clinician to suspect cycling CD in prepubertal patients. Confirmation of cyclic CD diagnosis is only possible during periods of relapse (hypercortisolemic state) and should be investigated according to the current diagnostic standard.